Growth monitoring of healthy and BSR-infected oil palm seedlings using ground-based LiDAR - Husin, Nur Azuan; Bejo, Siti Khairunniza; Md Noh, Normahnani; Ridu, Ray Clement (UPM Press, 2025)
The most threatening disease to the oil palm is Basal Stem Rot (BSR) disease caused by Ganoderma boninense. Besides matured oil palm trees, the oil palm seedlings are also susceptible to BSR disease. Therefore, it is crucial to detect the symptoms of the disease at an early stage, so that the infected plants can be treated immediately. This study focuses on growth monitoring to differentiate between the infected (INF) seedlings and non-infected (NONF) seedlings by using ground-based LiDAR. One hundred INF seedlings and 20 NONF seedlings were used in this study, where the NONF seedlings acted as a control. The parameters measured using LiDAR were the height, stem diameter and point density of the seedlings that were measured every two week intervals four times. The results showed there were significant differences in mean height and mean stem diameter between INF and NONF seedlings. Results from the LiDAR measurements were consistent with the manual measurements, where the correlations were more than 86%. In temporal measurements, the mean stem diameter for NONF seedlings consistently increased over the six weeks, while for INF seedlings it was inconsistent throughout the time. Furthermore, in the last three measurements, the mean point density of NONF seedlings was higher than INF seedlings which indicated better growth of non-infected seedlings compared to the infected seedlings.